Expression of TGF-β superfamily receptors in the retinal pigmented epithelium - Mitsuhiro,M. R. K. H. (1998)
SUMMARY Background: Retinal pigment epithelial (RPE) cells play an important role in the inflammatory response of the eye. Trans-forming growth factor-beta (TGF-β) and other members of the TGF-β superfamily are described to regulate some RPE cells functions. In this study the expression of TGF-β superfamily receptors in RPE cells at mRNA level was investigated Methods: RT-PCR technique was performed using mRNAs from D407 RPE cells (human RPE cell line) and HaCatTcells (human keratinocyte cell line used as positive control). Results: Expression of 6 type 1 receptors (TGF-β type I receptor, ALK-1, Activin type I receptor, activin type IB receptor, BMP type SA receptor, BMP type IB receptor), and 4 type II receptors (TGF-β type lI receptor, activin type II receptor, activin type IIB receptor, BMP type II receptor) were studied. The results demonstrated that TGF-β, activins and BMPs express their own specific receptors at mRNA level. Conclusions: The present study suggests that TGF-β superfamily members can exert effects on D407 RPE cells through their specific receptors.